Welcome to Westonci.ca, where curiosity meets expertise. Ask any question and receive fast, accurate answers from our knowledgeable community. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts.
Sagot :
To solve the system of equations using the elimination method, we must eliminate one of the variables to find the values of [tex]\(x\)[/tex] and [tex]\(y\)[/tex]. Let's follow these steps:
The given system of equations is:
[tex]\[ \begin{array}{r} 4x + y = 8 \quad \text{(1)} \\ 3x - 2y = 6 \quad \text{(2)} \end{array} \][/tex]
Step 1: Make the coefficients of [tex]\( y \)[/tex] the same
To eliminate [tex]\( y \)[/tex], we need to make the coefficients of [tex]\( y \)[/tex] in both equations equal. The least common multiple of the coefficients [tex]\(1\)[/tex] and [tex]\(-2\)[/tex] is [tex]\(2\)[/tex]. Thus, we will multiply equation (1) by 2 to make the coefficient of [tex]\( y \)[/tex] equal to 2 in absolute value.
[tex]\[ 2 \times (4x + y) = 2 \times 8 \][/tex]
[tex]\[ 8x + 2y = 16 \quad \text{(3)} \][/tex]
Now the system of equations looks like this:
[tex]\[ \begin{array}{r} 8x + 2y = 16 \quad \text{(3)} \\ 3x - 2y = 6 \quad \text{(2)} \end{array} \][/tex]
Step 2: Add the equations
Next, add equations (3) and (2) together to eliminate [tex]\( y \)[/tex].
[tex]\[ (8x + 2y) + (3x - 2y) = 16 + 6 \][/tex]
The [tex]\( 2y \)[/tex] and [tex]\( -2y \)[/tex] cancel out each other:
[tex]\[ 8x + 3x = 22 \][/tex]
[tex]\[ 11x = 22 \][/tex]
Step 3: Solve for [tex]\( x \)[/tex]
Divide both sides by 11:
[tex]\[ x = \frac{22}{11} \][/tex]
[tex]\[ x = 2 \][/tex]
Step 4: Substitute [tex]\( x \)[/tex] back to find [tex]\( y \)[/tex]
Now substitute [tex]\( x = 2 \)[/tex] back into one of the original equations to find [tex]\( y \)[/tex]. We will use equation (1):
[tex]\[ 4x + y = 8 \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ 4(2) + y = 8 \][/tex]
[tex]\[ 8 + y = 8 \][/tex]
Subtract 8 from both sides:
[tex]\[ y = 0 \][/tex]
Step 5: Verify the solution
We have found [tex]\( x = 2 \)[/tex] and [tex]\( y = 0 \)[/tex]. We should verify these values in the second equation to ensure they satisfy the original system.
Substitute [tex]\( x = 2 \)[/tex] and [tex]\( y = 0 \)[/tex] into equation (2):
[tex]\[ 3(2) - 2(0) = 6 \][/tex]
[tex]\[ 6 = 6 \][/tex]
Since both equations are satisfied, the solution to the system of equations is:
[tex]\[ x = 2, \quad y = 0 \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{D. \, x = 2, \, y = 0} \][/tex]
The given system of equations is:
[tex]\[ \begin{array}{r} 4x + y = 8 \quad \text{(1)} \\ 3x - 2y = 6 \quad \text{(2)} \end{array} \][/tex]
Step 1: Make the coefficients of [tex]\( y \)[/tex] the same
To eliminate [tex]\( y \)[/tex], we need to make the coefficients of [tex]\( y \)[/tex] in both equations equal. The least common multiple of the coefficients [tex]\(1\)[/tex] and [tex]\(-2\)[/tex] is [tex]\(2\)[/tex]. Thus, we will multiply equation (1) by 2 to make the coefficient of [tex]\( y \)[/tex] equal to 2 in absolute value.
[tex]\[ 2 \times (4x + y) = 2 \times 8 \][/tex]
[tex]\[ 8x + 2y = 16 \quad \text{(3)} \][/tex]
Now the system of equations looks like this:
[tex]\[ \begin{array}{r} 8x + 2y = 16 \quad \text{(3)} \\ 3x - 2y = 6 \quad \text{(2)} \end{array} \][/tex]
Step 2: Add the equations
Next, add equations (3) and (2) together to eliminate [tex]\( y \)[/tex].
[tex]\[ (8x + 2y) + (3x - 2y) = 16 + 6 \][/tex]
The [tex]\( 2y \)[/tex] and [tex]\( -2y \)[/tex] cancel out each other:
[tex]\[ 8x + 3x = 22 \][/tex]
[tex]\[ 11x = 22 \][/tex]
Step 3: Solve for [tex]\( x \)[/tex]
Divide both sides by 11:
[tex]\[ x = \frac{22}{11} \][/tex]
[tex]\[ x = 2 \][/tex]
Step 4: Substitute [tex]\( x \)[/tex] back to find [tex]\( y \)[/tex]
Now substitute [tex]\( x = 2 \)[/tex] back into one of the original equations to find [tex]\( y \)[/tex]. We will use equation (1):
[tex]\[ 4x + y = 8 \][/tex]
Substitute [tex]\( x = 2 \)[/tex]:
[tex]\[ 4(2) + y = 8 \][/tex]
[tex]\[ 8 + y = 8 \][/tex]
Subtract 8 from both sides:
[tex]\[ y = 0 \][/tex]
Step 5: Verify the solution
We have found [tex]\( x = 2 \)[/tex] and [tex]\( y = 0 \)[/tex]. We should verify these values in the second equation to ensure they satisfy the original system.
Substitute [tex]\( x = 2 \)[/tex] and [tex]\( y = 0 \)[/tex] into equation (2):
[tex]\[ 3(2) - 2(0) = 6 \][/tex]
[tex]\[ 6 = 6 \][/tex]
Since both equations are satisfied, the solution to the system of equations is:
[tex]\[ x = 2, \quad y = 0 \][/tex]
Therefore, the correct answer is:
[tex]\[ \boxed{D. \, x = 2, \, y = 0} \][/tex]
We appreciate your visit. Our platform is always here to offer accurate and reliable answers. Return anytime. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for trusting Westonci.ca. Don't forget to revisit us for more accurate and insightful answers.